Decision Support System for Determining the Best Hospital Nurses Grandmed Method Using Simple Additive Weighting (SAW) - Ester Simanjuntak; bosker Sinaga (Information Technology and Science (ITScience), 2020)
Decision support system is a combination of sources of individual intelligence with the ability of components to improve the quality of decisions. Also decision support systems are computer-based information systems for management decision-making that deal with semi-structural problems. The purpose of this study is to the make the application of nurse employees in Grandmed Hospital Based on the results of research that has been Discussed items, namely the Decision Support System for Determining the Best Nurses in Grandmed Hospital by Using the Simple Additive Wieghting (SAW) Method with the benefit of being Able to Facilitate the processing of the data and Facilitate nurse in Determination of the best nurse for a promotion to a nurse at Grandmed Hospital